Impact of PASSPORT learning model on improving students' mathematical communication skills - Jufri, Jufri; Asrial, Asrial; Johari, Asni; Kamid, Kamid (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Purpose: This study aims to analyze the effectiveness of the PASPOR learning model in improving students' mathematical communication skills compared to the Think-Talk-Write (TTW) model. Method: A quasi-experimental design was employed, involving two groups of PGSD students at Universitas Rokania: an experimental group taught using the PASPOR model and a control group taught using the TTW model. Data on mathematical communication skills were collected through pretests and posttests, and analyzed using normality, homogeneity, independent-sample t-tests, N-Gain calculations, and effect size, with the aid of SPSS 26. Findings: The findings indicate that students who learned with the PASPOR model showed a substantial improvement in their mathematical communication skills compared to those who experienced the TTW model. The enhancement was characterized by more active participation in collaborative learning, deeper engagement in discussion, and greater ability to express and reflect on mathematical ideas. Significance: The study highlights that the PASPOR learning model can serve as an effective and strategic alternative in mathematics education for developing students’ mathematical communication skills. This model not only fosters deeper conceptual understanding but also encourages critical thinking, teamwork, and effective communication, providing valuable insights for educators seeking to enhance mathematics instruction at various educational levels.